Knowledge and practices of mothers towards oral health of their 3-5 years children: a rural and urban comparative study - Srinivasan, Pavithra (International Journal Of Community Medicine And Public Health, 2022)
Background: Mothers are responsible for developing novel behaviors in children. The negligibility given to the primary dentition by the mothers in developing good oral hygiene practices was due to the lack of knowledge on its importance. The study aimed to compare the difference in knowledge and practices among rural and urban mothers towards the oral health of their children in the Kanchipuram and Chennai districts of Tamil Nadu. Methods: A community-based comparative cross-sectional study was carried out among 140 rural and 140 urban mothers of children between three to five years of age. The analysis of the study was carried out based on a 45-item questionnaire. The results used for comparison were based on descriptive statistics, chi-square test, independent t-test, one-way analysis of variance, and column proportion test (z test) using the statistical package for social science version 16.0. The significance level of all the tests was set at (p≤0.05). Results: The 37.1% of the rural and 79.3% of the urban mothers were found to have high knowledge. While only 6.4% of the rural and 22.1% of the urban mothers were found to have high practice. Also, there was a significant difference in knowledge (p=0.000) and practice (p=0.008) among different educational groups of rural and urban mothers as well. Conclusions: The majority of urban mothers have adequate knowledge regarding the oral hygiene of their children when compared with rural mothers. But the practices of both groups were drastically very low concerning their knowledge. The educational status of the mother had proved their advantage in their knowledge and practice.